2011
DOI: 10.1007/s10577-011-9264-x
|View full text |Cite
|
Sign up to set email alerts
|

Dmrt1 mutation causes a male-to-female sex reversal after the sex determination by Dmy in the medaka

Abstract: DMRT1, which is found in many vertebrates, exhibits testis-specific expression during the sexual differentiation period, suggesting a conserved function of DMRT1 in the testicular development of vertebrate gonads. However, functional analyses have been reported only in mammals. The current study focused on the Dmrt1 function in the teleost medaka, Oryzias latipes, which has an XX-XY sex determination system. Although medaka sex is determined by the presence or absence of the Y chromosome-specific gene Dmy, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 26 publications
2
88
0
1
Order By: Relevance
“…A large number of studies have confirmed that most male SD genes including dmy in medaka, are the duplications of Dmrt1 (dsx and mab-3 related transcription factor 1) [129,130]. It had been detected in medaka that dmrt1 mutation caused a male-to-female sex reversal, suggesting that dmrt1 should be essential for maintaining testis differentiation in the Dmy-triggered male sex determination pathway [131,132].…”
Section: Sex-determining (Sd) Genes In Fishmentioning
confidence: 99%
“…A large number of studies have confirmed that most male SD genes including dmy in medaka, are the duplications of Dmrt1 (dsx and mab-3 related transcription factor 1) [129,130]. It had been detected in medaka that dmrt1 mutation caused a male-to-female sex reversal, suggesting that dmrt1 should be essential for maintaining testis differentiation in the Dmy-triggered male sex determination pathway [131,132].…”
Section: Sex-determining (Sd) Genes In Fishmentioning
confidence: 99%
“…4 Functional classification of assembled unigenes based on Cluster of Orthologous Groups (COG) tools involved in fish male sexual development (Xia et al 2007;Ijiri et al 2008;Kamiya et al 2012;Hattori et al 2012;Shi et al 2012). In medaka, Dmrt1 mutation was reserved to result in a male-to-female sex reversal after the Dmy-initiated male WT1 Wilms tumor 1, Dmrt1 doublesex and mab-3 related transcription factor 1, Cyp19b cytochrome P450 aromatase 19b, Sox9 SRY-box containing gene 9, Foxl2 forkhead box L2, Sf1 steroidogenic factor 1, Vasa VASA, Dazl deleted in azoospermia-like, Piwi P-element induced wimpy testis, Nanos Nanos, ARA-α androgen receptor alpha, AMH ANTI-Müllerian hormone, AMHR2 anti-Müllerian hormone receptor 2, Fem-1 A protein fem-1 homolog A-like, Fem-1 B protein fem-1 homolog B-like, Fem-1 C protein fem-1 homolog C-like, Dax1 nuclear receptor subfamily 0 group B member 1, SPATA spermatogenesis-associated protein differentiation pathways (Masuyama et al 2012). In patagonian pejerrey, Amhy was detected in XY embryos as early as 5 days after hatching (dah), and gonadal sex differentiation began at 4 weeks after hatching (wah) in females and 6 wah in males (Hattori et al 2012).…”
Section: Characterization and Expression Of Sex Determination And Difmentioning
confidence: 99%
“…Dmrt1 (dsx and mab-3 related transcription factor 1) is a member of a gene family of putative transcription factors that share a highly conserved DNA binding domain (DM domain) believed to play critical roles in testis development and differentiation of vertebrates (Herpin and Schartl, 2011;Masuyama et al, 2012;Xia et al, 2007;Zarkower, 2013). Several sex determination and sex chromosome-linked genes in vertebrates such as Dmy in medaka (Matsuda et al, 2002;Nanda et al, 2002), DM-W in the W chromosome of African clawed frog (Yoshimoto et al, 2008), and Dmrt1 in the Z chromosome of birds (Smith et al, 2009), have been shown to be recently duplicated homologs of Dmrt1.…”
Section: Introductionmentioning
confidence: 99%